Strata-bound anorthites in the Dachang Sn-polymetallic ore field, Guangxi, China - Pan, Jiahua; Amstutz, Christian; Moh, Günter (Chinese journal of geochemistry, 1993)
From the petrological study of ore-hosting rocks which contain large anorthite crystals and the occurrence and chemical composition of anorthites and related minerals, the authors consider that the large anorthite crystals are of authigenic origin.
Gesehen am 15.02.2023